'Systems approach' plant breeding illustrated by trees. (February 2022) - Graudal, Lars; Dawson, Ian K.; Hale, Iago; Powell, Wayne; Hendre, Prasad; Jamnadass, Ramni
Abstract : The linkage in new and creative ways of existing plant breeding methods responsive to different global trends and values provides a 'systems approach' to address a broad set of global production challenges more effectively. Here, we illustrate such an approach through its application to trees, chosen because of their extensive diversity in features, uses, users, production contexts, and domestication pathways. We coin the resulting strategy 'tree diversity breeding' and consider it with reference to trends and values related to participation, environment, biotechnology, and markets as examples. Features of the approach for trees are applicable to plant breeding more widely, as we seek to address complex problems through strategic biodiversity use. Highlights: A 'systems approach' to plant breeding is increasingly recognised as required to address broad global challenges including the transgression of multiple planetary boundaries. In this opinion piece we describe a systems approach to plant breeding that is based on advancing novel and creative linkages between existing breeding methods that are oriented to multiple global trends and values. We illustrate our concept for how biodiversity can be mobilised strategically to address pressing global needs by considering the case study of tree genetic improvement. We choose 'tree diversity breeding' as our example based on the increasingly crucial roles of trees in supporting continued human development and the environment, and because of trees' enormous diversity that provides significant opportunities for a systems approach to genetic improvement.